taveRNA: a web suite for RNA algorithms and applications - Aksay, Cagri (Oxford University Press, 2007)
We present taveRNA, a web server package that hosts three RNA web services: alteRNA, inteRNA and pRuNA. alteRNA is a new alternative for RNA secondary structure prediction. It is based on a dynamic programming solution that minimizes the sum of energy density and free energy of an RNA structure. inteRNA is the first RNA–RNA interaction structure prediction web service. It also employs a dynamic programming algorithm to minimize the free energy of the resulting joint structure of the two interacting RNAs. Lastly, pRuNA is an efficient database pruning service; which given a query RNA, eliminates a significant portion of an ncRNA database and returns only a few ncRNAs as potential regulators. taveRNA is available at http://compbio.cs.sfu.ca/taverna.